The effects of endurance exercise in hypoxia on acid-base balance, potassium kinetics and carbohydrate metabolism - Sumi, D.; Kasai, N.; Ito, H.; Goto, K. (The Journal of Physical Fitness and Sports Medicine, 2018)
We investigated carbohydrate metabolism, acid-base balance and K+ kinetics in response to exercise under moderate hypoxic conditions in endurance athletes. [Methods] Nine trained endurance athletes [maximal oxygen uptake (VEO2max: 62.5 +/- 1.2 mL/kg/min) completed two different trials on different days, consisting of exercise under moderate hypoxia [fraction of inspired oxygen (FiO2) = 14.5%, HYPO) and exercise in normoxia (FiO2 = 20.9%, NOR). They performed high-intensity interval endurance exercise under hypoxic or normoxic conditions. Venous blood samples were obtained before exercise and during post-exercise period. The subjects consumed 13C-labeled glucose immediately before exercise, and we collected expired gas during exercise to determine 13C-excretion. [Results] The exercise-induced blood lactate elevation were significantly higher in the HYPO than in the NOR (P = 0.002). Bicarbonate ion concentrations (P = 0.002) and blood pH (P = 0.002) were significantly lower in the HYPO than in the NOR. There were no significant differences between the two trials for exercise-induced blood potassium elevation or 13C-excretion. [Conclusions] Endurance exercise under moderate hypoxic conditions elicited decline of blood pH. However, it did not augmented exercise-induced blood K + elevation and exogenous glucose oxidation (13C-excretion) compared with equivalent exercise under normoxic conditions among endurance athletes.